2003
DOI: 10.1046/j.1526-100x.2003.rec0260.x
|View full text |Cite
|
Sign up to set email alerts
|

Planted Riparian Buffer Zones in New Zealand: Do They Live Up to Expectations?

Abstract: River and stream rehabilitation projects are increasing in number, but the success or failure of these projects has rarely been evaluated, and the extent to which buffers can restore riparian and stream function and species composition is not well understood. In New Zealand the widespread conversion of forest to agricultural land has caused degradation of streams and riparian ecosystems. We assessed nine riparian buffer zone schemes in North Island, New Zealand that had been fenced and planted (age range from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
210
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(218 citation statements)
references
References 38 publications
5
210
0
2
Order By: Relevance
“…in a recent study, Harding et al (2006) did not find significant improvements in macroinvertebrate metrics as third order streams passed through short (250-350 m) forested corridors along agricultural streams in Canterbury, New Zealand. in their study of planted riparian zones, Parkyn et al (2003) concluded that riparian rehabilitation from the headwaters down to higher order streams may be necessary for restoration of stream health.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…in a recent study, Harding et al (2006) did not find significant improvements in macroinvertebrate metrics as third order streams passed through short (250-350 m) forested corridors along agricultural streams in Canterbury, New Zealand. in their study of planted riparian zones, Parkyn et al (2003) concluded that riparian rehabilitation from the headwaters down to higher order streams may be necessary for restoration of stream health.…”
Section: Discussionmentioning
confidence: 99%
“…High amounts of agricultural development in catchments usually lead to declines in biodiversity and biotic indices used as measures of stream health compared with streams in less developed or pristine catchments. More recently, studies have also examined the effects of restoration of native vegetation in catchments, particularly in riparian zones, on stream physicochemistry and biology (Parkyn et al 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive review of this literature is well beyond the scope of this paper, but numerous studies from around the world have investigated the impacts of forest management on riparian ecosystems (Iwata et al 2003;Parkyn et al 2003;Semlitsch and Bodie 2003;Olson et al 2007). These studies have variously demonstrated the importance of maintaining the integrity of riparian structural features such as shade and coarse woody debris, and of maintaining water quality parameters, to both riparian zone and in-stream values.…”
Section: Reflectionsmentioning
confidence: 99%
“…Such benefits may include the following: addition of organic matter, diversifying the trophic conditions; thermal regulation by forest canopy cover; structuring of habitat and provision of microhabitat; and buffer for nutrients and pollutant influx to the water course (Lowrance et al, 1984;Lowrance et al, 1997;Wenger et al, 1999). These functions have been evidenced only from local studies with field measurements (Storey and Cowley, 1997;Wallace et al, 1997;Parkyn et al, 2003;Dodds and Oakes, 2006;Rios and Bailey, 2006) and from some larger scale studies in strictly agricultural watersheds (Stewart et al, 2001;Wilson et al, 2008;Arnaiz et al, 2011). The cumulative watershed impact of forested riparian zones on stream nutrient levels is also acknowledged (Newbold et al, 2010;Curie et al, 2011;Wang et al, 2011), but remains poorly understood (Weller et al, 2011).…”
Section: Introductionmentioning
confidence: 99%